Use of Concepts and Terms in Research Plans : Effects of Enriched Metacognitive Genre Awareness through Concept Analysis Assignment - Katajamäki, Heli (VAKKI ry, 2021)
This paper discusses findings from a study conducted during an academic writing course for master’s students. The purpose of the study is to determine how the metacognitive genre awareness gained from an analysis assignment influenced students’ ability to write effective research plans. In this study, the focus is on concepts and terms, and the participating students were given two assignments: to analyse concepts of an existing master’s thesis in their field and to rewrite their research plans, taking into account the learning outcomes of the concept analysis assignment. This paper describes how students have changed the use of terms and concepts in their research plans. The data consists of two versions of research plans written in Finnish by 14 students of University of Vaasa in spring 2019. The analysis showed that students' research plans changed and became more detailed: students modified their research plans by adding central concepts, generic concepts and specific concepts, and by specifying relationships between concepts or adding definitions. They also eliminated synonymous terms. Based on these results, a conclusion can be drawn that a concept analysis assignment is a tool that is effective in enriching students’ metacognitive genre awareness of the use of terms and concepts when teaching academic writing.
Keywords: concept; genre knowledge; metacognitive genre awareness; academic writing; concept analysis